Silicon Nutrition to Rice (Oryza sativa L.) Alleviates Fe, Mn and Al Toxicity in Laterite Derived Rice Soils - Biju Joseph; R. Gladis, Sainath Nagula (Journal of the Indian Society of Soil Science, 2016)
Toxicity of iron (Fe), manganese (Mn) and aluminium (Al) are widespread in laterite derived rice soils of Kerala. Plants undergo severe abiotic stress due to the toxicity of these elements. The current study was carried out to investigate the influence of silicon (Si) application to rice on alleviating toxicity of Fe, Mn and Al in laterite-derived wetland rice soils of northern Kerala. A pot culture experiment replicated thrice was laid out in complete randomized design with the application of Si and boron (B) as soil and foliar spray. Rice variety ‘Aishwarya’ was used as the test crop. The available Fe, Mn, Al and Si in soil, and the content and uptake of these elements by the plants were studied. The crop was grown till maturity and grain and straw yield were recorded. The results indicated a significant decline in available Fe content in soil in treatments receiving Si compared to control. Decline was to the tune of 31 per cent due to the foliar application of potassium silicate @ 0.5% spray + borax 0.5%. Similar results were obtained with respect to available Mn and exchangeable Al content in soil. Higher Si content in soil was obtained with the soil application of calcium silicate @ 4 g kg-1 soil which was superior to foliar application of potassium silicate. The Fe and Mn contents in straw and grain were decreased with application of Si, while its uptake by plant alone was significantly increased. The grain and straw yields of rice were also significantly increased with the soil application of calcium silicate and foliar application of potassium silicate.